Biodiversity Of Marine Yeasts Isolated From Coral Sand In Truong Sa Archipelago, Khanh Hoa Province, Vietnam - T. T. Do Hong; H. T. Nguyen; V. Le Thang; T. K. Nguyen Thanh; X. T. Phan (Geography, Environment, Sustainability)
Truong Sa archipelago of Vietnam are very diverse in microorganisms, however, compared to aquatic microorganisms (sea water, sediment, etc) terrestrial microorganisms (soil, coral sand, etc) has received little attention. This study focuses on assessing the biodiversity of marine yeasts in coral sand samples collected at some islands in Truong Sa archipelago. From nine coral sand samples collected at three islands: Song Tu island (three samples), Sinh Ton island (three samples), Truong Sa island (three samples), twenty – four strains of marine yeasts were isolated. The number of marine yeast strains isolated in Truong Sa island was the highest (ten strains). Sample CS9 had the highest number of strains. These strains were grouped into eight groups based on colony and cell morphology and fourteen groups by DNA fingerprinting. The results showed that there are strains in the same group according to morphology but belong to two different groups according to fingerprinting. Otherwise, some strains have different morphology but are grouped according to fingerprinting. The fourteen yeast strains representing groups by DNA fingerprinting were closely related to fourteen different yeast species and belong to ten yeast genera (Yamadazyma, Candida, Trichosporon, Saccharomyces, Kodamaea, Rhodotorula, Rhodosporidium, Aureobasidium, Meyerozyma, Pichia). Among them, the genus Candida accounted for the highest number. This is the first study on marine yeasts in coral sand in Truong Sa archipelago, Vietnam. This study can be a premise for further studies on marine yeast in different fields such as medicine, agriculture, environment, etc.